Co-Parenting Quality and Parenting Stress as Predictors of Child Behavioral Adjustment - Turan, Selva; Benali, Youssef (Applied Family Therapy Journal (AFTJ), 2025)
Objective: This study aimed to investigate the predictive roles of co-parenting quality and parenting stress in relation to child behavioral adjustment among parents in Morocco. Methods: A correlational descriptive design was employed involving a sample of 396 parents selected based on Krejcie and Morgan’s sampling table. Participants completed three standardized instruments: the Child Behavior Checklist (CBCL) to assess child behavioral problems, the Parenting Stress Index–Short Form (PSI-SF) to measure perceived parenting stress, and the Co-parenting Relationship Scale (CRS) to evaluate co-parenting quality. Data were analyzed using SPSS version 27. Pearson correlation coefficients were computed to examine the bivariate associations between the dependent variable and each independent variable. Multiple linear regression was then conducted to evaluate the joint predictive power of parenting stress and co-parenting quality on child behavioral adjustment, with all assumptions for regression analysis thoroughly checked and confirmed. Findings: Results showed a significant positive correlation between parenting stress and child behavioral problems (r = .56, p < .01), and a significant negative correlation between co-parenting quality and child behavioral problems (r = –.42, p < .01). Multiple regression analysis revealed that parenting stress (β = .48, t = 8.60, p < .01) and co-parenting quality (β = –.31, t = –6.75, p < .01) were both significant predictors of child behavioral adjustment. The overall model was significant (F(2, 393) = 129.72, p < .01), explaining 40% of the variance in child behavioral outcomes (R² = .40, Adjusted R² = .39). Conclusion: The findings highlight the critical roles of both relational and psychological parenting factors in child development. Interventions aiming to reduce parenting stress and enhance co-parenting quality may be effective in improving behavioral outcomes in children, especially in non-Western cultural contexts like Morocco.